Ketone-Based Metabolic Therapy: Is Increased NAD+ a Primary Mechanism? - Elamin, Marwa; Ruskin, David N.; Masino, Susan A.; Sacchetti, Paola (Frontiers in Molecular Neuroscience, 2017)
The ketogenic diet’s anticonvulsant effects have been well-documented for nearly a century, including in randomized controlled trials. Some patients become seizure-free and some remain so after diet cessation. Many recent studies have explored its expanded therapeutic potential in diverse neurological disorders, yet no mechanism(s) of action have been established. The diet’s high fat, low carbohydrate composition promotes ketone bodies as an energy source and improves mitochondrial function and biogenesis. Cellular energy production depends on the metabolic coenzyme nicotinamide adenine dinucleotide (NAD), a marker for mitochondrial and cellular health. Furthermore, NAD activates downstream signaling pathways (such as the sirtuin enzymes) associated with major benefits such as longevity and reduced inflammation; thus, increasing NAD is a coveted therapeutic endpoint. Based on differential NAD+ utilization during glucose- versus ketone body-based acetyl-CoA generation for entry into the tricarboxylic cycle, we propose that a ketogenic diet will increase the NAD+/NADH ratio. When rats were fed ad libitum ketogenic diet significant increases in hippocampal NAD+/NADH ratio and blood ketone bodies were detected already at two days and remained elevated at three weeks, indicating an early and persistent metabolic shift. Based on diverse published literature and these initial data we suggest that increased NAD during ketolytic metabolism may be a primary mechanism behind the beneficial effects of this metabolic therapy in a variety of brain disorders and in promoting health and longevity.